Determination of Baylisascaris schroederi Infection in Wild Giant Pandas by an Accurate and Sensitive PCR/CE-SSCP Method - Zhang, Wenping (Public Library of Science, 2012)
It has been recognized that other than habitat loss, degradation and fragmentation, the infection of the roundworm Baylisascaris schroederi (B. schroederi) is one of the major causes of death in wild giant pandas. However, the prevalence and intensity of the parasite infection has been inconsistently reported through a method that uses sedimentation-floatation followed by a microscope examination. This method fails to accurately determine infection because there are many bamboo residues and/or few B. schroederi eggs in the examined fecal samples. In the present study, we adopted a method that uses PCR and capillary electrophoresis combined with a single-strand conformation polymorphism analysis (PCR/CE-SSCP) to detect B. schroederi infection in wild giant pandas at a nature reserve, and compared it to the traditional microscope approach. The PCR specifically amplified a single band of 279-bp from both fecal samples and positive controls, which was confirmed by sequence analysis to correspond to the mitochondrial COII gene of B. schroederi. Moreover, it was demonstrated that the amount of genomic DNA was linearly correlated with the peak area of the CE-SSCP analysis. Thus, our adopted method can reliably detect the infectious prevalence and intensity of B. schroederi in wild giant pandas. The prevalence of B. schroederi was found to be 54% in the 91 fecal samples examined, and 48% in the fecal samples of 31 identified individual giant pandas. Infectious intensities of the 91 fecal samples were detected to range from 2.8 to 959.2 units/gram, and from 4.8 to 959.2 units/gram in the fecal samples of the 31 identified giant pandas. For comparison, by using the traditional microscope method, the prevalence of B. schroederi was found to be only 33% in the 91 fecal samples, 32% in the fecal samples of the 31 identified giant pandas, and no reliable infectious intensity was observed.